Breakdown mechanism of γ-Al2O3 on Ni2Al3 coatings exposed in a biomass fired power plant. (1st July 2020) - Wu, D.L.; Dahl, K.V.; Grumsen, F.B.; Christiansen, T.L.; Montgomery, M.; Hald, J.
Graphical abstract: Highlights: In-plant testing of Ni2 Al3 coated superheater tubes were performed in a biomass-firing power plant for one year. In the protective areas, a 30–50 nm γ-Al2 O3 layer was present on the surface and no Al depletion was observed below the oxide layer. At locations with corrosion attack, no alumina scale was present and an amorphous K–O surface layer with a thickness of 200–250 nm was found. γ-Al2 O3 was broken down by reaction with KCl(g) resulting in potassium aluminate and volatile AlCl3 was formed by the migration of Cl. A molten salt consisting of KCl-AlCl3 can lead to alumina fluxing and further penetration of corrosive species into the coating. Abstract: A Ni2 Al3 coated tube was exposed in a wood firing power plant for 7100 h. The exposure resulted in protective behaviour in most areas, while corrosion attack occurred in local areas. In areas exhibiting protective behaviour, a 30−50 nm thick γ-Al2 O3 layer was found, and a 200−250 nm K–O rich amorphous layer was identified in the corroded area. A corrosion mechanism is suggested: γ-Al2 O3 was broken down by reaction with KCl(g) resulting in formation of potassium aluminate. Migration of Cl through potassium aluminate resulted in formation of volatile AlCl3 . KCl-AlCl3 then led to alumina fluxing and further corrosion attack.